The basement geology of the Porcupine High – new geochronological constraints from the westernmost Caledonides - David Chew; Shannon Dennehy; Shane Tyrrell; J. Stephen Daly; Rémi Rateau; Eszter Badenszki; Martin J. Whitehouse; Kerryming Sun; Paul Guyett (Precambrian Research, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Benthic Macroinvertebrates as Bioindicators of Stream Health Within the Central African Copperbelt - Kennedy O. Ouma; Agabu Shane; Concillia Monde; Stephen Syampungani (Water, Air, & Soil Pollution, 2025)
Globally, stream ecosystem health in mining regions, including the Central African Copperbelt (CACB), is threatened by increased aquatic metal pollution. Stream biomonitoring and bioassessment offers an eco-friendly nature-based approach to determine the aquatic ecological conditions and inform management interventions in mining landscapes. This study conducted monthly between May 2022 and April 2023, explored the taxonomic and functional responses of macroinvertebrates as bioindicators of the ecological condition of four streams in the north-western Zambian Copperbelt of the CACB. 252 sediment samples were collected and analysed for metals. 144 macroinvertebrate samples were collected to determine their taxonomic and functional traits. ANOVA (analysis-of-variance), SIMPER (similarity-percentage), ANOSIM (analysis-of-similarities), CCA (canonical correspondence analysis) and multidimensional biotic index analyses were conducted to correlate environmental and biotic variables. Metal concentrations (mg/kg) in sediments followed the order As (5.27) < Pb (5.75) < Zn (44.6) < Ni (89.3) < Cu (187.5). From ANOVA, the macroinvertebrate community was significantly dominated by Insecta families, mostly Diptera (23.3%) and Coleoptera (16.7%). Trophically, predators significantly dominated in the order Odonata (34.7%) > Hemiptera (31.8%) > Diptera (18.9%). SIMPER depicted a strong influence of Cu, EC, velocity, sediment texture and organic matter on macroinvertebrate diversity and spatial distribution. ANOSIM indicated the highest community dissimilarity at the most impacted stream (KYABR). Habitat assessment metrics, including ZISS-1, ASPT, and EPT/Chironomidae ratio, registered a “good ecological status” with the presence of pollution-sensitive taxa (Helodidae and Perlidae), in concordance with environmental variables, confirming the suitability of macroinvertebrates as proxy bioindicators of stream health in mining landscapes. The study confirms the potential of macroinvertebrates, as potential bioindicators of stream health in mining landscapes. Their diversity and distribution is strongly influenced by Cu, EC, velocity, and sediment characteristics while habitat assessment metrics indicate a "good ecological status" despite moderate metal contamination.

Assessment of laser ablation and solution-based ICP-MS applications commonly used in otolith geochemical analysis of marine teleosts - Michelle Zapp Sluis; Daniel L. Lippi; Phillip J. Sanchez; Nathaniel R. Miller; Shane A. Stephens; Beatrice P. Ferreira; Jay R. Rooker (Frontiers in Marine Science, 2025)
Different applications of inductively coupled plasma mass spectrometry (ICP-MS) have the potential to influence results of otolith geochemical assays. Laser ablation and solution-based ICP-MS were compared on paired otoliths from three species of juvenile fish representative of estuarine (red drum [ Sciaenops ocellatus ]), coastal/reef (gray parrotfish [ Sparisoma axillare ]), and pelagic (blackfin tuna [ Thunnus atlanticus ]) ecosystems. Additionally, two laser ablation techniques (continuous line transects and series of spots) were performed to determine whether these two commonly used approaches yielded comparable results. No significant differences existed between line transects and spots for any of the three species investigated, with high correlations occurring for all otolith element:Ca (E:Ca) values retained for statistical testing (Mg:Ca, Mn:Ca, Sr:Ca, Ba:Ca), suggesting that both laser ablation techniques produced equivalent otolith E:Ca values. In contrast, pronounced differences in E:Ca values were detected between laser ablation (across otolith transverse section) and solution-based (whole otolith dilution) applications on paired sagittal otoliths. While some E:Ca discrepancies varied among the three species, overall otolith E:Ca values were higher when quantified by laser ablation, except for Ba:Ca which tended to be higher when analyzed by solution-based ICP-MS. Differences observed between laser ablation and solution-based applications are the result of the allometric growth of the otolith and may become more pronounced in older, larger individuals as the differential growth along the otolith axes becomes less uniform with age. Further, laser ablation techniques can examine life history profiles and discern fluctuations over time, proving a preferred application over solution-based analysis.

Estuarine-coastal connectivity and partial migration of southern flounder in the Gulf of Mexico - Christopher Steffen; Shane Stephens; Michael A. Dance; Daniel L. Lippi; Christine C. Jensen; R.J. David Wells; Jay R. Rooker (Estuarine, Coastal and Shelf Science, 2023)

Crustal basement terranes under the Taupō Volcanic Zone, New Zealand: Context for hydrothermal and magmatic processes - Nick Mortimer; Bruce L.A. Charlier; Shane M. Rooyakkers; Rose E. Turnbull; Colin J.N. Wilson; Marianne Negrini; Stephen Bannister; Sarah D. Milicich; Isabelle Chambefort; Craig A. Miller; Geoff Kilgour (Journal of Volcanology and Geothermal Research, 2023)

Learning from hydrological models’ challenges: A case study from the Nelson basin model intercomparison project - Mohamed Ismaiel Ahmed; Tricia Stadnyk; Alain Pietroniro; Hervé Awoye; Ajay Bajracharya; Juliane Mai; Bryan A. Tolson; Hongren Shen; James R. Craig; Mark Gervais; Kevin Sagan; Shane Wruth; et al. (Journal of Hydrology, 2023)

Ex Vivo Modeling of Atrioventricular Valve Mechanics in Single Ventricle Physiology - Stephen C. Moye; Sumanth Kidambi; James Y. Lee; Teaghan H. Cowles; Shane D. Gilligan-Steinberg; Amelia Y. Bryan; Rob Wilkerson; Y. Joseph Woo; Michael R. Ma (Annals of Biomedical Engineering, 2023)

Animal population decline and recovery after severe fire: Relating ecological and life history traits with expert estimates of population impacts from the Australian 2019-20 megafires - Michelle Ensbey; Sarah Legge; Chris J. Jolly; Stephen T. Garnett; Rachael V. Gallagher; Mark Lintermans; Dale G. Nimmo; Libby Rumpff; Ben C. Scheele; Nick S. Whiterod; John C.Z. Woinarski; Shane T. Ahyong; et al. (Biological Conservation, 2023)

Large and in charge: cortisol levels vary with sex, diet, and body mass in an Antarctic predator, the leopard seal - Emily S. Sperou; Daniel E. Crocker; Renato Borras-Chavez; Daniel P. Costa; Michael E. Goebel; Shane B. Kanatous; Douglas J. Krause; Stephen J. Trumble; Sarah S. Kienle (Frontiers in Marine Science, 2023)
Evaluating physiological responses in the context of a species’ life history, demographics, and ecology is essential to understanding the health of individuals and populations. Here, we measured the main mammalian glucocorticoid, cortisol, in an elusive Antarctic apex predator, the leopard seal ( Hydrurga leptonyx ). We also examined intraspecific variation in cortisol based on life history (sex), morphometrics (body mass, body condition), and ecological traits ( δ 15 N, δ 13 C). To do this, blood samples, life history traits, and morphometric data were collected from 19 individual leopard seals off the Western Antarctic Peninsula. We found that adult leopard seals have remarkably high cortisol concentrations (100.35 ± 16.72 μg/dL), showing the highest circulating cortisol concentration ever reported for a pinniped: 147 μg/dL in an adult male. Leopard seal cortisol concentrations varied with sex, body mass, and diet. Large adult females had significantly lower cortisol (94.49 ± 10.12 μg/dL) than adult males (120.85 ± 6.20 μg/dL). Similarly, leopard seals with higher isotope values (i.e., adult females, δ 15 N: 11.35 ± 0.69‰) had lower cortisol concentrations than seals with lower isotope values (i.e., adult males, δ 15 N: 10.14 ± 1.65‰). Furthermore, we compared cortisol concentrations across 26 closely related Arctoid taxa (i.e., mustelids, bears, and pinnipeds) with comparable data. Leopard seals had the highest mean cortisol concentrations that were 1.25 to 50 times higher than other Arctoids. More broadly, Antarctic ice seals (Lobodontini: leopard seal, Ross seal, Weddell seal, crabeater seal) had higher cortisol concentrations compared to other pinnipeds and Arctoid species. Therefore, high cortisol is a characteristic of all lobodontines and may be a specialized adaptation within this Antarctic-dwelling clade. Together, our results highlight exceptionally high cortisol concentrations in leopard seals (and across lobodontines) and reveal high variability in cortisol concentrations among individuals from a single location. This information provides the context for understanding how leopard seal physiology changes with life history, ecology, and morphology and sets the foundation for assessing their physiology in the context of a rapidly changing Antarctic environment.

Land use change increases contaminant sequestration in blue carbon sediments - Stephen R. Conrad; Isaac R. Santos; Shane A. White; Ceylena J. Holloway; Dylan R. Brown; Praktan D. Wadnerkar; Rogger E. Correa; Rebecca L. Woodrow; Christian J. Sanders (Science of The Total Environment, 2023)

Whiskers provide time-series of toxic and essential trace elements, Se:Hg molar ratios, and stable isotope values of an apex Antarctic predator, the leopard seal - Patrick Charapata; Casey T. Clark; Nathan Miller; Sarah S. Kienle; Daniel P. Costa; Michael E. Goebel; Heather Gunn; Emily S. Sperou; Shane B. Kanatous; Daniel E. Crocker; Renato Borras-Chavez; Stephen J. Trumble (Science of The Total Environment, 2023)

Rolling Deck to Repository: Supporting the marine science community with data management services from academic research expeditions - Suzanne M. Carbotte; Suzanne O’Hara; Karen Stocks; P. Dru Clark; Laura Stolp; Shawn R. Smith; Kristen Briggs; Rebecca Hudak; Emily Miller; Chris J. Olson; Neville Shane; Rafael Uribe; et al. (Frontiers in Marine Science, 2022)
Direct observations of the oceans acquired on oceanographic research ships operated across the international community support fundamental research into the many disciplines of ocean science and provide essential information for monitoring the health of the oceans. A comprehensive knowledge base is needed to support the responsible stewardship of the oceans with easy access to all data acquired globally. In the United States, the multidisciplinary shipboard sensor data routinely acquired each year on the fleet of coastal, regional and global ranging vessels supporting academic marine research are managed by the Rolling Deck to Repository (R2R, rvdata.us) program. With over a decade of operations, the R2R program has developed a robust routinized system to transform diverse data contributions from different marine data providers into a standardized and comprehensive collection of global-ranging observations of marine atmosphere, ocean, seafloor and subseafloor properties that is openly available to the international research community. In this article we describe the elements and framework of the R2R program and the services provided. To manage all expeditions conducted annually, a fleet-wide approach has been developed using data distributions submitted from marine operators with a data management workflow designed to maximize automation of data curation. Other design goals are to improve the completeness and consistency of the data and metadata archived, to support data citability, provenance tracking and interoperable data access aligned with FAIR (findable, accessible, interoperable, reusable) recommendations, and to facilitate delivery of data from the fleet for global data syntheses. Findings from a collection-level review of changes in data acquisition practices and quality over the past decade are presented. Lessons learned from R2R operations are also discussed including the benefits of designing data curation around the routine practices of data providers, approaches for ensuring preservation of a more complete data collection with a high level of FAIRness, and the opportunities for homogenization of datasets from the fleet so that they can support the broadest re-use of data across a diverse user community.

The conservation impacts of ecological disturbance: Time‐bound estimates of population loss and recovery for fauna affected by the 2019–2020 Australian megafires - Sarah Legge; Libby Rumpff; John C. Z. Woinarski; Nick S. Whiterod; Michelle Ward; Darren G. Southwell; Ben C. Scheele; Dale G. Nimmo; Mark Lintermans; Hayley M. Geyle; Stephen T. Garnett; Brittany Hayward‐Brown; et al. (Global Ecology and Biogeography, 2022)
Aim After environmental disasters, species with large population losses may need urgent protection to prevent extinction and support recovery. Following the 2019–2020 Australian megafires, we estimated population losses and recovery in fire‐affected fauna, to inform conservation status assessments and management. Location Temperate and subtropical Australia. Time period 2019–2030 and beyond. Major taxa Australian terrestrial and freshwater vertebrates; one invertebrate group. Methods From > 1,050 fire‐affected taxa, we selected 173 whose distributions substantially overlapped the fire extent. We estimated the proportion of each taxon’s distribution affected by fires, using fire severity and aquatic impact mapping, and new distribution mapping. Using expert elicitation informed by evidence of responses to previous wildfires, we estimated local population responses to fires of varying severity. We combined the spatial and elicitation data to estimate overall population loss and recovery trajectories, and thus indicate potential eligibility for listing as threatened, or uplisting, under Australian legislation. Results We estimate that the 2019–2020 Australian megafires caused, or contributed to, population declines that make 70–82 taxa eligible for listing as threatened; and another 21–27 taxa eligible for uplisting. If so‐listed, this represents a 22–26% increase in Australian statutory lists of threatened terrestrial and freshwater vertebrates and spiny crayfish, and uplisting for 8–10% of threatened taxa. Such changes would cause an abrupt worsening of underlying trajectories in vertebrates, as measured by Red List Indices. We predict that 54–88% of 173 assessed taxa will not recover to pre‐fire population size within 10 years/three generations. Main conclusions We suggest the 2019–2020 Australian megafires have worsened the conservation prospects for many species. Of the 91 taxa recommended for listing/uplisting consideration, 84 are now under formal review through national processes. Improving predictions about taxon vulnerability with empirical data on population responses, reducing the likelihood of future catastrophic events and mitigating their impacts on biodiversity, are critical.

Age group differences in blubber fatty acid profiles in northern elephant seals (Mirounga angustirostris) - Aaron W. Kirkpatrick; Daniel E. Crocker; Shane B. Kanatous; Kerri J. Smith; Sarah S. Kienle; Stephen J. Trumble (Frontiers in Marine Science, 2022)
Northern elephant seals ( Mirounga angustirostris ), like many marine mammals, rely on internal lipid stores, specifically fatty acids (FAs) stored in the blubber layer, to meet metabolic needs. The energetic demands of northern elephant seals vary with ontogeny, as each life-history stage experiences different metabolic requirements due to development, growth, and breeding. To date, no comprehensive study has reported on changes in blubber FA profiles across northern elephant seal age groups or sex. Therefore, our objective was to determine how blubber FAs differ across ontogeny and sex in northern elephant seals. As a sexually dimorphic mammal, northern elephant seals go through sex-specific ontogenetic changes in morphology and physiology; we hypothesized that these changes would be reflected in their FAs profiles. To determine this, FAs profiles were compared from full blubber cores collected from 79 northern elephant seals across four age groups. We provide the first evidence of blubber fatty acids differing across ontogeny as NES transition from young, developing seals to mature fully developed adults. However, we did not find differences in blubber FAs profiles between the sexes. Monounsaturated fatty acids (MUFAs) are found in the highest proportions across all NES age classes and sexes, followed by SFAs and PUFAs; this highlights the important role MUFAs play in maintaining fluidity of the blubber layer and in thermoregulation. The individual FAs with the highest concentrations (C16:1, C18:1n9 and C16:0) in northern elephant seal blubber are similar to those in other marine mammals. Weaned pup FAs profiles were significantly different from all other age classes; adults and juveniles also showed age-specific differences. Specifically, weaned pups had the highest proportions of SFAs and the lowest proportions of PUFA, suggesting use of PUFAs to aid development. Each life history stage of NES is interconnected to previous and future stages, making FA accumulation, mobilization, and storage an important process throughout an individual’s life. Further, any changes to this process can have cascading consequences throughout ontogeny in this species. Future monitoring of the FA composition of blubber across age classes could potentially indicate the costs of different environmental changes on blubber storage in NES.

Plasticity in the morphometrics and movements of an Antarctic apex predator, the leopard seal - Sarah S. Kienle; Michael E. Goebel; Erin LaBrecque; Renato Borras-Chavez; Stephen J. Trumble; Shane B. Kanatous; Daniel E. Crocker; Daniel P. Costa (Frontiers in Marine Science, 2022)
Animals that display plasticity in behavioral, ecological, and morphological traits are better poised to cope with environmental disturbances. Here, we examined individual plasticity and intraspecific variation in the morphometrics, movement patterns, and dive behavior of an enigmatic apex predator, the leopard seal ( Hydrurga leptonyx ). Satellite/GPS tags and time-depth recorders were deployed on 22 leopard seals off the Western Antarctic Peninsula. Adult female leopard seals were significantly larger (454±59 kg) and longer (302±11 cm) than adult males (302±22 kg, 276±11 cm). As females were 50% larger than their male counterparts, leopard seals are therefore one of the most extreme examples of female-biased sexual size dimorphism in marine mammals. Female leopard seals also spent more time hauled-out on land and ice than males. In the austral spring/summer, three adult female leopard seals hauled-out on ice for 10+ days, which likely represent the first satellite tracks of parturition and lactation for the species. While we found sex-based differences in morphometrics and haul-out durations, other variables, including maximum distance traveled and dive parameters, did not vary by sex. Regardless of sex, some leopard seals remained in near-shore habitats, traveling less than 50 kilometers, while other leopard seals traveled up to 1,700 kilometers away from the tagging location. Overall, leopard seals were short (3.0±0.7 min) and shallow (29±8 m) divers. However, within this general pattern, some individual leopard seals primarily used short, shallow dives, while others switched between short, shallow dives and long, deep dives. We also recorded the single deepest and longest dive made by any leopard seal—1, 256 meters for 25 minutes. Together, our results showcased high plasticity among leopard seals tagged in a single location. These flexible behaviors and traits may offer leopard seals, an ice-associated apex predator, resilience to the rapidly changing Southern Ocean.

Assessing pesticide, trace metal, and arsenic contamination in soils and dam sediments in a rapidly expanding horticultural area in Australia - Stephen R. Conrad; Shane A. White; Isaac R. Santos; Christian J. Sanders (Environmental Geochemistry and Health, 2021)

Locally abundant, endangered Mariana swiftlets impact the abundance, behavior, and body condition of an invasive predator - Page E. Klug; Amy A. Yackel Adams; Shane R. Siers; Kevin M. Brindock; Stephen M. Mosher; M. J. Mazurek; William C. Pitt; Robert N. Reed (Oecologia, 2021)

Trends in Growth Modeling in Fisheries Science - Shane A. Flinn; Stephen R. Midway (Fishes, 2021)
Growth models estimate life history parameters (e.g., growth rates and asymptotic size) that are used in the management of fisheries stocks. Traditionally in fisheries science, it was common to fit one growth model—the von Bertalanffy growth model—to size-at-age data. However, in recent years, fisheries science has seen an increase in the number of growth models available and the evaluation of multiple growth models for a given species or study. We reviewed n = 196 peer-reviewed age and growth studies and n = 50 NOAA (National Oceanic and Atmospheric Administration) regional stock assessments to examine trends in the use of growth models and model selection in fisheries over time. Our results indicate that the total number of age and growth studies increased annually since 1988 with a slight proportional increase in the use of multi-model frameworks. Information theoretic approaches are replacing goodness-of-fit and a priori model selection in fisheries studies; however, this trend is not reflected in NOAA stock assessments, which almost exclusively rely on the von Bertalanffy growth model. Covariates such as system (e.g., marine or fresh), location of study, diet, family, maximum age, and range of age data used in model fitting did not contribute to which model was ultimately the best fitting, suggesting that there are no large-scale patterns of specific growth models being applied to species with common life histories or other attributes. Given the importance and ubiquity of growth modeling to fisheries science, a historical and contemporary understanding of the practice is critical to evaluate improvements that have been made and future challenges.

Contrasting Radium-Derived Groundwater Exchange and Nutrient Lateral Fluxes in a Natural Mangrove Versus an Artificial Canal - Praktan D. Wadnerkar; Bayartungalag Batsaikhan; Stephen R. Conrad; Kay Davis; Rogger E. Correa; Ceylena Holloway; Shane A. White; Christian J. Sanders; Isaac R. Santos (Estuaries and Coasts, 2021)

SMART Cables for Observing the Global Ocean: Science and Implementation - Bruce M. Howe; Brian K. Arbic; Jérome Aucan; Christopher R. Barnes; Nigel Bayliff; Nathan Becker; Rhett Butler; Laurie Doyle; Shane Elipot; Gregory C. Johnson; Felix Landerer; Stephen Lentz; et al. (Frontiers in Marine Science, 2019)

Nutrient and Trace Metal Fluxes into Estuarine Sediments Linked to Historical and Expanding Agricultural Activity (Hearnes Lake, Australia) - Stephen R. Conrad; Isaac R. Santos; Shane White; Christian J. Sanders (Estuaries and Coasts, 2019)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Longitudinal patterns of potentially inappropriate prescribing in early old-aged people - Christina Raae Hansen; Stephen Byrne; Shane Cullinan; Denis O’Mahony; Laura J. Sahm; Patricia M. Kearney (European Journal of Clinical Pharmacology, 2018)

A late glacial Antarctic climate teleconnection and variable Holocene seasonality at Lake Pupuke, Auckland, New Zealand - Thomas Stephens; Daniel Atkin; Paul Augustinus; Philip Shane; Andrew Lorrey; Alayne Street-Perrott; Andreas Nilsson; Ian Snowball (Journal of Paleolimnology, 2012)

A diatom-inferred record of reduced effective precipitation during the Last Glacial Coldest Phase (28.8–18.0 cal kyr BP) and increasing Holocene seasonality at Lake Pupuke, Auckland, New Zealand - Thomas Stephens; Daniel Atkin; Ursula Cochran; Paul Augustinus; Michael Reid; Andrew Lorrey; Philip Shane; Alayne Street-Perrott (Journal of Paleolimnology, 2012)

Contrasting effects of sunitinib within in vivo models of metastasis - Jonathan C. Welti; Thomas Powles; Shane Foo; Morgane Gourlaouen; Natasha Preece; Julie Foster; Sophia Frentzas; Demelza Bird; Kevin Sharpe; Antoinette van Weverwijk; David Robertson; Julie Soffe; et al. (Angiogenesis, 2012)

Forest Management, Engineering, and Operations - Randy Kolka; Matt Powers; John Bradford; Brian Palik; Marty Jurgensen; Dalia Abbas; Tom Gallagher; Stephen Ambagis; Finto Antony; Lewis Jordan; Richard Daniels; Laurie Schimleck; et al. (Journal of Forestry, 2011)
9Forests represent a major global C sink, and forest management strategies that maximize carbon storage offer one avenue for mitigating increases in atmospheric carbon dioxide concentrations. Our understanding of relationships between forest management, productivity, carbon storage, and stand age, however, is limited. We established research plots in a chronosequence of thinned and unmanaged red pine stands in northern Minnesota to study patterns of carbon storage, and the major fluxes that influence carbon sequestration. We completed an inventory of all major C pools across a chronosequence of 57 red pine stands ages 9-306 years on the Chippewa National Forest in the fall of 2009. Results indicate total ecosystem C pools increase as red pine stands age for at least 150 years, and on-site C storage in thinned stands appears similar to unmanaged stands of comparable ages, despite different age-related trends in the live tree and forest floor pools. Thinned stands may have the potential to store more C than unmanaged stands in old age when C removed during harvesting is added into the total ecosystem C pool.

Sand-binding roots in Haemodoraceae: global survey and morphology in a phylogenetic context - Rhian J. Smith; Stephen D. Hopper; Michael W. Shane (Plant and Soil, 2011)

Model selection and model averaging in behavioural ecology: the utility of the IT-AIC framework - Shane A. Richards; Mark J. Whittingham; Philip A. Stephens (Behavioral Ecology and Sociobiology, 2011)

Effects of Cooking on Radiocesium in Fish from the Savannah River: Exposure Differences for the Public - Joanna Burger; Karen F. Gaines; C. Shane Boring; J. Snodgrass; W. L. Stephens; M. Gochfeld (Archives of Environmental Contamination and Toxicology, 2004)

Elevated genetic heterogeneity and Pleistocene climatic instability: inferences from nrDNA in New Zealand Coprosma (Rubiaceae) - Stephen R. Wichman; Shane D. Wright; Ewen K. Cameron; D. Jeannette Keeling; Richard C. Gardner (Journal of Biogeography, 2002)
Aim To examine patterns of hybridization and genotype mixing within the genus Coprosma J.R.Forst. & G.Forst. (Rubiaceae). Location New Zealand Methods Nucleotide sequence was determined for the internal transcribed spacer (ITS) and external transcribed spacer (ETS) regions of nuclear ribosomal DNA for fifty individuals from thirty‐six taxa within the New Zealand component of the genus Coprosma . Results Mixed sequences were found to be widespread in Coprosma . Direct sequencing of ITS polymerase chain reaction (PCR) products from seven polyploid taxa showed evidence of sequence mixtures. Cloning and sequencing of individual PCR products from two polyploids confirmed the presence of multiple templates, one of which corresponded to that of a diploid. Intra‐individual heterogeneity was also seen in a hybrid diploid taxon, with the mixed nucleotides corresponding to those of the parental lineages. Finally the ITS sequences of twenty‐two diploid taxa showed that eleven contained intra‐individual heterogeneity. Conclusions We conclude that the widespread occurrence of sequence mixtures in Coprosma results from of frequent hybridization. We also conclude that concerted evolution of the ITS and ETS regions is depressed. We propose that these characteristics evolved as a mechanism to maintain high levels of heterogeneity and suggest that this is adaptive for Coprosma in climatically unstable and physically complex New Zealand landscapes. These landscapes have been subjected to repeated oscillations between stadial and interstadial environments during the Pleistocene.

Expression of the mitogen-activated protein kinase kinase ZmMEK1 in the primary root of maize - Shane C. Hardin; Stephen M. Wolniak (Planta, 2001)

Stepping stones to Hawaii: a trans‐equatorial dispersal pathway for Metrosideros (Myrtaceae) inferred from nrDNA (ITS+ETS) - Shane D. Wright; Catherine G. Yong; Stephen R. Wichman; John W. Dawson; Richard C. Gardner (Journal of Biogeography, 2001)
Aim The majority of Hawaii's plants are derived from the south and west of the Pacific rim, suggesting that at least some of the founders have crossed the climatic discontinuity at the equator. However, the pathways of these dispersal events are not well understood. We sought to elucidate such a pathway for the plant genus Metrosideros Banks ex Gaertn., which appears to have colonized Hawaii from New Zealand. Location We have previously analysed the internal transcribed spacer (ITS) sequence of nrDNA for thirty‐six taxa of Metrosideros subgenus Metrosideros distributed across Melanesia and Polynesia. Further we collected two taxa from the Austral and Marquesas Islands. Methods Phylogenetic analysis was undertaken using both the ITS and external transcribed spacer (ETS) regions of nrDNA for twenty‐three taxa from Polynesia and East Melanesia. Results The increased resolution achieved by combining ETS data with that of ITS allowed discrimination of two subclades in eastern Oceania. One subclade groups all the Hawaiian taxa together with M. collina (J. R. & G. Forst.) A. Gray from the Marquesas Islands. Main conclusions From an origin in New Zealand, the woody angiosperm Metrosideros is likely to have crossed the equator to Hawaii using a staging point in the remote Marquesas Islands. Colonization of Hawaii by the wind‐borne seed of these plants has been achieved against the flow of the prevailing Trade winds north of the equator. A possible climatic mechanism for this dispersal is described.

Symposia lectures - F. Parak; A. Ostermann; G. U. Nienhaus; Nobuo Niimura; William A. Eaton; Stephen J. Hagen; Eric R. Henry; James Hofrichter; Gouri Jas; Lisa Lapidus; Victor Muñoz; Chih-chen Wang; et al. (Journal of Biosciences, 1999)

Molecular cloning and characterization of maize ZmMEK1, a protein kinase with a catalytic domain homologous to mitogen- and stress-activated protein kinase kinases - Shane C. Hardin; Stephen M. Wolniak (Planta, 1998)